SRL-Based Mentoring to Strengthen Students’ Academic Independence in Islamic Boarding Schools - Fitria Puji Atma Dewi Ali; Farhan Qomarudin; Widya Astuti Sari; Agnes Nila Kisti; Linda Dwi Novita Wardani; Roni Susanto (Amalee: Indonesian Journal of Community Research and Engagement, 2026)
This community service program aimed to strengthen students’ academic independence through Self-Regulated Learning (SRL)-based mentoring at Darul Khoir Islamic Boarding School. The program involved 20 students aged 15–20 years who actively participated in pesantren learning activities. It employed a Participatory Action Research (PAR) approach comprising planning, action, observation, and reflection. Activities included a needs assessment, SRL socialization, intensive mentoring, monitoring, and evaluation involving students, ustadz, and pesantren administrators. Data were collected through participatory observation, interviews, documentation, and reflective evaluation. The findings showed that SRL mentoring improved students’ learning behavior and academic independence. Evaluation results revealed that 85% of participants established consistent memorization targets, 80% maintained regular muroja’ah schedules, 75% demonstrated better readiness for memorization deposits, and 70% became more active in independently reviewing nahwu-shorof and yellow-book materials after religious study sessions. The novelty of this program lies in integrating SRL principles with the traditional learning culture of Islamic boarding schools, particularly in Qur’an memorization and classical Islamic studies. This contextual mentoring model offers a practical and replicable strategy for fostering sustainable independent learning in Qur’an-oriented and salaf-based pesantren